Hand position during chest compression in infantile piglets – Do you need to encircle the chest with the 2-thumb-technique? - Brandon Kowal; Megan O’Reilly; Tze-Fun Lee; Georg M. Schmölzer (Resuscitation Plus)
Background: The Pediatric Life Support Consensus on Science With Treatment Recommendations states that chest compressions (CC) be performed with the 2-thumb-encircling and if the chest can not be encircled the 2-finger-technique. Aim: To compare the hemodynamic effects of four different compression methods during CC in a piglet model of infant asphyxia. Methods: Nine asphyxiated infant piglets were randomized to CC with 2-thumb-encircling, 2-thumb-, 2-finger-, and one-hand-techniques for one minute at each technique. CC were performed manually while hemodynamic parameters were continuously measured. Results: Nine infantile piglets (age 5–10 days, weight 2.1–3.0 kg) were included in the study. The 2-thumb-technique and 2-thumb-encircling technique both had a significantly higher mean (SD) ejection fraction of 52.6 (31.2)% and 64.4 (30.6)% compared to the one-hand-technique with 26.6 (15.1)% (p = 0.005). The 2-thumb-encircling technique also had a significantly higher ejection fraction compared to the 2-finger-technique with values of 64.4 (30.6)% and 30.4 (12.1)%, respectively (p = 0.005). Furthermore, 2-thumb-technique and 2-thumb-encircling technique produced significantly higher carotid blood flow and dp/dtmax, and significantly lower dp/dtmin compared to the one-hand- and 2-finger-techniques. Conclusion: The 2-thumb- and 2-thumb-encircling-techniques produced significantly higher ejection fraction, carotid blood flow, and dp/dtmax, and lower dp/dtmin compared to the 2-finger- and one-hand-techniques. Encircling the chest during the 2-thumb-technique produces similar hemodynamic effects compared to the 2-thumb-technique without encircling.